Business performance of culinary MSMEs based on innovation capability and information technology in Cianjur Regency - Tini Kartini; Endang Silaningsih; Suci Nuralita (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the influence of innovation capability and information technology on the business performance of culinary SMEs in Cianjur Regency. A quantitative approach with a descriptive-verificative design was employed, using data collected from 100 culinary SME owners selected through proportionate stratified random sampling. Data were gathered through questionnaires, interviews, observations, and documentation and analyzed using multiple linear regression. The findings reveal that both innovation capability and information technology exert positive and significant effects on business performance, both individually and jointly. Among the two predictors, innovation capability demonstrates the strongest influence, highlighting its critical role in enhancing competitiveness and organizational performance. The results suggest that SMEs capable of continuously developing innovative products and processes while effectively leveraging information technology are better positioned to improve operational efficiency, respond to changing market demands, and achieve sustainable business growth. This study contributes to the literature on SME competitiveness by providing empirical evidence on the complementary roles of innovation and digital technology in strengthening business performance. The findings also offer practical implications for SME managers and policymakers seeking to foster sustainable enterprise development through innovation-driven and technology-enabled business strategies. Keywords: Innovation Capability; Information Technology; Business Performance; Culinary SMEs